The Aggregate Effects of the Hartz Reforms in Germany - Matthias Sebastian Hertweck; Oliver Sigrist (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper quantifies the impact of the Hartz reforms on matching efficiency, using monthly SOEP gross worker flows (1983-2009). We show that, until the early 2000s, close to 60% of changes in the unemployment rate are due to changes in the inflow rate (job separation). On the contrary, since the implementation of the reforms in the mid-2000s, the importance of the outflow rate (job finding) has been steadily increasing. This indicates that matching efficiency has improved substantially in recent years. Results from an estimated matching function - pointing to efficiency gains of more than 20% - corroborate this finding.
Keywords: E24; E32; J64; 330